2009
DOI: 10.1002/adsc.200900399
|View full text |Cite
|
Sign up to set email alerts
|

4‐Aminothiourea Prolinol tert‐Butyldiphenylsilyl Ether: A Chiral Secondary Amine‐Thiourea as Organocatalyst for Enantioselective anti‐Mannich Reactions

Abstract: anti-Selective Mannich reactions of N-pmethoxyphenyl (PMP)-protected a-iminoglyoxylate with unmodified aldehydes or ketones were effectively catalyzed by 4-aminothiourea prolinol tert-butyldiphenylsilyl ether. The reactions led to chiral bamino carbonyl compounds in high yields (up to 94%), excellent diastereo-and enantioselectivities (up to 98% de and > 99% ee). The study demonstrated for the first time that direct Mannich-type reactions of unmodified aldehydes or ketones to aiminoglyoxylate can be promoted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…Peng and co-workers have developed a chiral secondary amine-thiourea organocatalyst, 4-aminothiourea prolinol tert-butyldiphenylsilyl ether 26, which was applied to the direct anti-selective asymmetric Mannich reaction (Scheme 6) [45]. The direct Mannich reaction of cyclohexanone with N-p-methoxyphenyl a-iminoglyoxylate proceeded smoothly in the presence of 5-10 mol% of 26 in CH 2 ClCH 2 Cl to afford anti-product in a high yield and with excellent diastereo-and enantioselectivity.…”
Section: Asymmetric Mannich Reactionmentioning
confidence: 99%
“…Peng and co-workers have developed a chiral secondary amine-thiourea organocatalyst, 4-aminothiourea prolinol tert-butyldiphenylsilyl ether 26, which was applied to the direct anti-selective asymmetric Mannich reaction (Scheme 6) [45]. The direct Mannich reaction of cyclohexanone with N-p-methoxyphenyl a-iminoglyoxylate proceeded smoothly in the presence of 5-10 mol% of 26 in CH 2 ClCH 2 Cl to afford anti-product in a high yield and with excellent diastereo-and enantioselectivity.…”
Section: Asymmetric Mannich Reactionmentioning
confidence: 99%
“…Pyrrolidines 17 26 and 18 27 that work through the same model have also been reported by Blanchet and Maruoka, independently. More recently, the thiourea‐based catalyst 19 that combines structural features of catalysts 13 and 18 has been reported by Peng for the same reaction 28. Accordingly, the main limitation of all these contributions is that only α‐imino esters appear to be sufficiently reactive to give Mannich adducts with both chemical and stereochemical efficiency 29.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the thiourea-based catalyst 19 that combines structural features of catalysts 13 and 18 has been reported by Peng for the same reaction. [28] Accordingly, the main limitation of all these contributions is that only aimino esters appear to be sufficiently reactive to give Mannich adducts with both chemical and stereochemical efficiency. [29] One solution has been recently presented by Maruoka who has revealed that N-Boc (tert-butoxycarbonyl) imines from arylaldehydes may be utilized in the Mannich reaction by using chiral sulfonamide 14.…”
Section: Resultsmentioning
confidence: 99%
“…When ketones were used as substrates, moderate to good yields were obtained but the enantioselectivities are excellent (up to 99% ee). [20] With realization of the importance of the Mannich reaction in the synthesis of b-amino acid derivatives, Gellman [21a] and Córdova [21b] successfully exploited the enantioselective organocatalytic method for the Mannich reaction between formaldehyde-derived Nbenzyl-N-(methoxymethyl)A C H T U N G T R E N N U N G (phenyl)methanamine (35) and aldehydes. Formaldehyde does not form stable imines, so the use of N-benzyl-N-(methoxymethyl)-A C H T U N G T R E N N U N G (phenyl)methanamine (35) as a precursor of the methylene iminium species is practical.…”
Section: Mannich Reactionsmentioning
confidence: 99%